Penatalaksanaan Pasien Rheumatoid Arthritis Berbasis Evidence Based Nursing : Studi Kasus - Sari, Sinta Purnama; Rezkiki, Fitrianola (Universitas Fort De Kock Bukittinggi, 2020)
Background: One of the chronic diseases is rheumatoid arthritis (RA) is the most common auto immune disease, which is inflammation of the joints that occurs in adulthood and the elderly. According to the American Collage Of Rheumatology, 2015, rheumatoid arthritis has a significant negative impact on the ability to move, both work and household chores and affect quality of life and increase mortality. Indications of an increase in cases of rheumatism in the community one of them because of the lack of family attention to the prevention and care of family members who have rheumatic diseases. Aim: To find out Family Nursing Care with the Application of Complementary Therapy in Rheumatism Cases in one of Kanagarian Sumatera Barat. Method: In implementation, complementary therapy is applied to Rheumatic patients, namely through routine health checks, physical activity, rheumatic diet, gymnastics elderly, and consumption fro. Results: Rheumatism pain that was experienced Ny. Z has decreased from pain scale 6 (moderate) to 2 (mild) after ingestion of the frost for ± 6 days. Conclusion: : The application of complementary therapies showed improvement in patients suffering from rheumatism, therefore, the application of evidence-based nursing in providing nursing care is recommended.